Satisfaction with in-patient psychiatric services. Relationship to patient and treatment factors. - Greenwood, N; Key, A; Burns, T; Bristow, M; Sedgwick, P (1999)
BACKGROUND: There is growing concern about patient satisfaction with psychiatric in-patient provision. This paper measures satisfaction in psychiatric in-patients and its relationships with patient characteristics and ward experiences. AIMS: To: (a) measure overall in-patient satisfaction; (b) examine its relationship to in-patient experiences; and (c) examine its relationship to patient factors. METHOD: Four hundred and thirty-three patients were interviewed. Satisfaction was assessed by a single quest on, the Client Satisfaction Questionnaire (CSQ) and by a semistructured interview. RESULTS: Over three-quarters of the patients were satisfied, but two-thirds reported adverse events. Females, younger patients and those detained were more dissatisfied. No significant relationship was found for ethnic group. Results were similar in the mental hospital and district general hospital. CONCLUSIONS: There remain problems with satisfaction scales. Qualitative approaches to examine patients' experiences in hospital and the causes of dissatisfaction are recommended.